Investigating the potential of using solid waste generated from stone cutting factories for phenol removal from wastewater: A study of adsorption kinetics and isotherms - Nada Al-Ananzeh (18024469) (2023)
Remarkably toxic, phenol requires efficient elimination from water. This study investigates the utilization of solid waste generated by stone-cutting factories for extracting phenol from wastewater. The solid waste underwent thermal treatment at 105 °C for 3 h for characterization. Batch adsorption experiments systematically assessed parameters like phenol concentration, adsorbent mass, contact time, temperature, and pH. Optimal removal transpired at pH 7.5, reaching equilibrium within 4 h. Phenol uptake equilibrium values were 8.1, 13.3, 16.2, 20.2, and 28.1 mg/g for initial concentrations of 50, 100, 150, 200, and 300 mg/L, respectively using 1 g of adsorbent at ambient temperature. The Langmuir model fit acceptably, yet the Freundlich model surpassed it. The most suitable kinetics model for phenol adsorption was the pseudo-second-order. The nature of the adsorption process was endothermic. Importantly, this study pioneers the promising application of solid waste generated from stone-cutting factories as an adsorbent material for effective phenol removal, offering a sustainable approach. Notably, no previous study has been conducted on phenol removal from wastewater using this specific adsorbent, rendering this work pivotal in exploring its potential. This solid waste presents an economical, readily available, and environmentally benign material for the adsorption process, expected to exhibit substantial adsorption capacity. Other Information Published in: Results in Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rineng.2023.101404